Standardization of fetal ultrasound biometry measurements: improving the quality and consistency of measurements. - Sarris, I; Ioannou, C; Dighe, M; Mitidieri, A; Oberto, M; Qingqing, W; Shah, J; Sohoni, S; Al Zidjali, W; Hoch, L; Altman, D; Papageorghiou, A (2011)
OBJECTIVE: To assess whether a standardization exercise prior to commencing a fetal growth study involving multiple sonographers can reduce interobserver variation. METHODS: In preparation for an international study assessing fetal growth, nine experienced sonographers from eight countries participated in a standardization exercise consisting of theoretical and practical sessions. Each performed a set of seven standard fetal measurements on pregnant volunteers at 20-37 weeks' gestation, and these were repeated by the lead sonographer; all measurements were taken in a blinded fashion. After this the sonographers had hands-on practice and feedback sessions on other volunteers. This process was repeated three times. Measurement differences between sonographers and the lead sonographer, expressed as a gestational-age-specific Z-score, between the first and third scans were compared using the Wilcoxon signed ranks test, and variance was assessed using Pitman's test. Interobserver agreement was also assessed using the intraclass correlation coefficient (ICC), and all images were scored for quality in a blinded fashion. RESULTS: At baseline the level of agreement and image scoring were high. A significant reduction in the differences between sonographers and the lead sonographer were seen for fetal biometry overall (head circumference, abdominal circumference and femur length) between the first and third scans (median Z-scores, 0.46 and 0.24; P = 0.005), and a reduction in the variance was also observed (P < 0.001). The ICCs for measurement pairs for every fetal measurement showed a clear trend of increasing ICC (better agreement) with consecutive training scan sessions, although no improvement in image scores was seen. CONCLUSION: Even for experienced sonographers, a standardization exercise before starting a study of fetal biometry can improve consistency of measurements. This could be of relevance for studies assessing fetal growth in multicenter sites.